Craniocerebral Disproportion Corrected With Biparietal Distraction Osteogenesis - Jordan R. Whittles, BS; Timar Mascio, BS; James Baumgartner, MD; Joseph Lopez, MD, MBA, FAAP, FACS (Plastic and Reconstructive Surgery, Global Open)
Summary:. Ventriculoperitoneal shunt therapy represents a lifesaving neurosurgical intervention in pediatric patients with hydrocephalus. Although necessary, research indicates that shunting may be associated with a spectrum of craniocerebral disproportion from frank craniosynostosis to later presenting neurofunctional symptoms and headaches. The surgical management of craniosynostosis is generally treated according to provider and institutional preference; however, shunt therapy presents difficulties for typical vault remodeling procedures. In this report, we describe the utility of a biparietal distraction osteogenesis configuration for the treatment of craniocerebral disproportion in 2 patients. A parallel arrangement of an anterior and a posterior set of 2 distractors allows for a doubling of the typical expansion of the parietal diameter. This method effectively alleviates the scaphocephaly without disruption of the shunt site. We propose our repair for the indication of sagittal craniosynostosis in the shunted patient.